Quality of pediatric clinical practice guidelines - Yali Liu; Yuan Zhang; Shu Wang; Ling Liu; Gang Che; Jiahui Niu; Yuan Ma (BMC, 2021)
Abstract Background There is a lack of a comprehensive evaluation for pediatric clinical practice guidelines (CPGs) published in recent years. Here, we assessed the quality of pediatric CPGs, considering factors that might affect their quality. The aim of the study is to promote a more coherent development and application of CPGs. Methods Pediatric CPGs published in PubMed, MedLive, Guidelines International Network, National Institute for Health and Care Excellence, and World Health Organization between 2017 and 2019 were searched and collected. Paired researchers conducted screening, data extraction, and quality assessment using the Appraisal of Guidelines for Research and Evaluation II (AGREE II). Linear regression analysis determined the factors affecting CPGs' quality. Results The study included a total of 216 CPGs, which achieved a mean score of 4.26 out of 7 points (60.86%) in the AGREE II assessment. Only 6.48% of the CPGs reached the "recommend" level. The remaining 69.91% should have been modified before recommendation, while the other 23.61% did not reach the recommended level at all. The overall quality of recent pediatric CPGs was higher than previously, and the proportion of CPGs with low-quality decreased over time. However, there were still too few CPGs that reached a high-quality level. The "applicability" and "rigor of development" domains had generally low scores. CPGs formulated by developing countries or regions, those that are not under an organizations or groups responsibility, and those that used non-evidence-based methods were found to be associated with poorer quality in different domains as independent or combinational factors. Conclusions The quality of pediatric CPGs still needs to be improved. Specifically, a quality control before applying new CPGs should be essential to ensure their quality and applicability.